The appropriateness of monetary instruments employed by Caribbean central banks - preliminary investigation - Birchwood, Anthony ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Investigates whether the instruments used for the conduct of monetary policy have been effective in absorbing liquidity and whether there have been negative implications for the stability of the financial sector, resulting from the use of these instruments. Utilises panel data consisting of 13 banks located in Guyana, Jamaica and Trinidad and Tobago. The sample is drawn for the period 1998 to 1996.